WAYS OF IMPROVING THE FOREIGN ECONOMIC MARKETING STRATEGY OF UKRAINIAN LOGISTICS ENTERPRISES - MOZGOVA, Galyna; SHTYKH, Yevheniya (Herald of Khmelnytskyi National University. Economic sciences, 2022)
This article was directed to the analysis of marketing strategies of enterprises engaged in the export of logistics services to the foreign market. The importance of marketing strategy research was substantiated. Also, it was confirmed that any company has its own marketing strategy. The concept of "marketing strategy" was defined. The main classic marketing strategies were described. Michael Porter’s competitive strategies were explored. According to F. Kotler, the main strategies of behaviour of competitors in the market were described. The classification of growth marketing strategies according to the main strategic directions was described. It was concluded that currently modern enterprises cannot use only one marketing strategy to achieve success. The process of how Ukrainian enterprises implement transport services on the foreign market was analysed in its entirety. A positive trend of growth in the volume of foreign trade in logistics services of Ukraine and the predominance of exports over imports to the foreign market was determined. The trend of demand for Ukrainian transport services on the foreign market was assessed. According to statistical calculations of the latest financial indicators, it was determined that foreign consumers have a demand for transport services offered by Ukrainian logistics companies. A study of marketing statistics showed that Ukrainian logistics companies lag behind foreign ones in terms of marketing strategies. On the example of the most profitable Ukrainian logistics companies, the main common features of conducting business activities were highlighted. The main marketing tools used by profitable logistics companies were identified. The main tools of "digital marketing" for attracting potential customers of logistics companies were listed. The importance of using "digital marketing" tools to supplement the marketing strategy of enterprises in the modern trends of the foreign market was substantiated.